Physical Fitness Profiles of Beginner Volleyball Players in a Developing Regional Academy: Insights for Youth Performance Development - Ade Rahmat; Muhammad Suhairi; Rio Wardhani (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This study aimed to profile the physical fitness characteristics — muscular strength, cardiorespiratory endurance, agility, speed, and coordination — of beginner volleyball players at Yuso Volleyball Academy, West Kalimantan, Indonesia, and to examine sex-based differences in order to inform evidence-based youth performance development. Materials and methods: A descriptive cross-sectional survey design was employed. Twenty-five beginner volleyball players (boys, n = 11; girls, n = 14; aged 8–12 years) were assessed using a standardised test battery comprising the 60-second push-up test (strength), the 12-minute Cooper run (cardiorespiratory endurance), the Illinois agility test (agility), the 30-metre sprint (speed), and the volleyball wall-pass test over 30 seconds (sport-specific coordination). Descriptive statistics (mean ± standard deviation) were computed, and independent-samples t-tests with Cohen's d effect sizes were used to examine sex differences (α = 0.05). Results: Forty-seven studies (n = 3,284; 19 countries; 2000–2024) met inclusion criteria; 42 were pooled Boys outperformed girls in strength (41.36 ± 4.82 vs. 32.14 ± 3.97 repetitions; p < 0.001; d = 2.11), endurance (2,520 ± 180 vs. 2,210 ± 165 m; p < 0.001; d = 1.81), and speed (4.32 ± 0.24 vs. 4.68 ± 0.29 s; p = 0.003; d = 1.34). Differences in agility (10.21 ± 0.56 vs. 10.45 ± 0.61 s; p = 0.32) and coordination (28.09 ± 3.11 vs. 26.21 ± 2.88 repetitions; p = 0.13) were not statistically significant. Across the cohort, agility, speed, and coordination were classified as 'good', whereas cardiorespiratory endurance was the lowest-rated component ('fair'). Conclusions: Beginner volleyball players at the academy displayed a fair-to-good overall fitness profile, with cardiorespiratory endurance identified as the most prominent developmental priority for both sexes. Agility, speed, and coordination should be maintained through varied, sport-specific stimuli, while strength training should be progressively individualised, with particular attention to upper-body conditioning in girls. The findings provide a regionally relevant baseline that can be integrated into structured long-term athlete development pathways.